Indigenous and Roman Catholic Canonizations of Nicholas Black Elk: Postcolonial Issues and Implications of Black Elk Speaks - Stoeber, Michael (Theological studies, 2020)
This article explores questions surrounding the status and teachings of Nick Black Elk, in dialogue with certain postcolonial and decoloniality theorists, as well as with commentators on Black Elk’s spirituality. It highlights liberation spirituality and theology in analyzing the religious hybridity of Black Elk and his actions of decoloniality. It also shows how Black Elk’s recent nomination for Roman Catholic canonization might continue to support certain shifts in various areas of Christian spirituality in light of Lakota influences: to respectful approaches to visionary mysticism and dreams; to positive affirmations of embodied spirituality; to ecological connections, consciousness and responsibility; and to a transformed sense of spiritual intimacy with nature.